GRASI DALAM KONSEP TUJUAN PEMIDANAAN - Titik Suharti (Perspektif, 2005)
Grasi represent one of form of is reason of crime liquidator and represent the medium to get the pardon in the form of change, extenuation, reduction, or abolition of crime execution which have been knocked down to be punished by pursuant to justice decision obtained the legal force remain to, as arranged in Law No 22 Thn 2002 about Grasi.